KEDUDUKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN - Amna Emda (Lantanida Journal, 2017)
Learning is an activity involving teachers and students. The success of teaching and learning process are influenced by student learning motivation. The existence of student learning motivation will give spirit and learning becomes more focused for students. Building intrinsic motivation in students will be better than extrinsic motivation. By students' intrinsic motivation to learn because of the sincerity of their hearts, the positive results of learning efforts that will shown. However, extrinsic motivation also determines the interest of students in learning. When students have a desire to learn but the extrinsic factors do not support, the student will lose his spirits. Both intrinsic and extrinsic factors can determine the success of students in the learning process. Motivation is an energy change within the person characterized by effective arausal and antisipatory goal reaction. Motivation will push, move and direct students to learn. Students who have a high learning motivation will do activities in acquiring knowledge. Motivation will arouse the interest of students to learn. Motivation has the function of which is to (1) encourage students to move in order to get maximum results, and (2) as referring to carry out activities in achieving the objectives specific objectives. Motivation has traits include: resilient in the face of adversity, diligently not easily bored and others. The existence of the learning motivation greatly affected the success of the learning process. Students can reach a good study achievements on him when there is motivation to learn. Therefore the motivation has a very important position in learning.